Clinical profile and short-term outcome of perinatally asphyxiated term neonates in a tertiary hospital in Southern Kerala - Joseph, Susy; Bindusha, S; Radhika, S; Krishnan, Rekha; Kumar, Sobha (Indian Journal of Child Health, 2017)
Introduction: In India, in spite of improvement in perinatal-neonatal care, perinatal asphyxia accounts for 23% of the neonatal deaths. Objective: The objective of the study was to study the clinical profile and short-term outcome of perinatally asphyxiated term neonates. Materials and Methods: This prospective study conducted at a tertiary care teaching hospital in Southern Kerala from June 2011 to June 2015. 120 term asphyxiated neonates fulfilling the inclusion criteria admitted in the NICU were followed up till death or survival. Results: 49.2% babies were inborn and 50.8% babies were outborn. Of the total, 53 (44.2%) were delivered vaginally, 54 (45%) by cesarean section, and 13 (10.8%) by instrumental delivery. Antenatal complications were seen in 58 (48.3%) and intrapartum complications in 93 (77.5%). Hypoxic ischemic encephalopathy (HIE) was diagnosed in 78.3%, with HIE 1 in 19.3%, HIE 2 in 27.5%, and HIE 3 in 31.6%. The mortality was 31 (25.8%) and it was more in out born babies compared to inborn. Factors associated with development of severe HIE (HIE 3) were male gender (p=0.0057), need for endotracheal intubation (p=0.0114), instrumental delivery and pH